Apical periodontitis after intense bruxism - Madline P. Gund; Karl-Thomas Wrbas; Matthias Hannig; Stefan Rupf (BMC, 2022)
Abstract Background Bruxism is known to cause masticatory muscle pain, temporomandibular joint pain, headaches, mechanical tooth wear, prosthodontic complications and cracked teeth. Less known to the practitioner, and described only experimentally in literature, is that bruxism can also damage the pulp. To our knowledge, this is the first known clinical case of a patient developing apical periodontitis due to bruxism. Case presentation This article presents the case and successful treatment of a 28-year-old healthy male patient with apical periodontitis on teeth 36 and 46 requiring root canal treatment after an intense phase of bruxism. Due to an unclear diagnosis, treatment had been delayed. Conclusions Incomprehensible tooth pain can be the result of bruxism. Practitioners need to be informed that intense bruxism can possibly lead to apical periodontitis. It is important, therefore, that a thorough anamnesis is collected and taken into account during diagnostics.